(untitled) (Clinics, 2010)
OBJECTIVE: To determine the impact of delirium on post-discharge mortality in hospitalized older patients. INTRODUCTION: Delirium is frequent in hospitalized older patients and correlates with high hospital mortality. There are only a few studies about its impact on post-discharge mortality. METHODS: This is a prospective study of patients over 60 years old who were hospitalized in the Geriatric Unit at Hospital das Clínicas of São Paulo between May 2006 and March 2007. Upon admission, demographics, comorbidities, number of drugs taken, and serum albumin concentration were evaluated for each patient. Delirium was diagnosed according to the DSM-IV criteria. Patients were divided into group A (with delirium) and group B (without delirium). One year after discharge, the patients or their caregivers were contacted to assess days of survival. RESULTS: The sample included 199 patients, 66 (33%) of whom developed delirium (Group A). After one year, 33 (50%) group A patients had died, and 45 (33.8%) group B patients had died (p = 0.03). There was a significant statistical difference in average age (p = 0.001) and immobility (p ; 80 years (p = 0.029), albumin concentration < 3.5 g/dl (p = 0.001) and immobility (p = 0.007). CONCLUSION: Delirium is associated with higher post-discharge mortality as a dependent predictor.